IMPLEMENTATION OF SUSTAINABLE TOURISM IN SUPPORTING QUALITY TOURISM IN TIPANG VILLAGE - Rosianna Sianipar; Juliana Juliana; Nova Bernedetta Sitorus; Rosdiana Pakpahan; Meitolo Hulu (Jurnal Ekonomi, 2023)
This study aimed to examine the tourism potential of Tipang Village and the implementation of sustainable tourism. This research uses qualitative methods. The data collection technique used in this study was an interview. The resource persons in this interview were the Pokdarwis of Tipang Village and the local community. Observations were made of the potential tourist attraction in Tipang Tourism Village. Sustainable Tourism in Tipang Village is still a potential. This potential needs to be increased and managed more optimally with collaboration and synergy from various stakeholders. Based on information from the management of the Tipang Tourism Village, it is known that the need for more support from various parties is the current obstacle. Lack of funding is also a major obstacle currently experienced by Tipang Village. To keep it running, operational costs are obtained from the sales of homestays and coffee shops. Management of the coffee shop itself capital is still needed to manage it, so for now, the management of the coffee shop is stopped and focuses on homestay marketing. Another obstacle is needing to increase the number of visits. The Tipang Village manager needs to have village regulations governing the payment of entrance tickets so that they are not considered illegal levies. Some of the discussions that were carried out resulted in the statement that Tipang Village still needs to be eligible for an entrance fee because the facilities are also inadequate at the tourist attractions in Tipang Village. Thus, according to the manager of Tipang Village, implementing sustainable tourism still requires a long journey.